SOSIALISASI SENAM KAKI TERHADAP SENSITIVITAS KAKI DALAM MENURUNKAN KADAR GLUKOSA DARAH DARAH TERHADAP PENDERITA DIABETES MELLITUS TIPE 2 DI RUANG RENGAS DENGKLOK RSUD KARAWANG - Grace Evelyn; Herwed Nelson; Eva Wulan Sari (Bajang Institute, 2024)
Type 2 Diabetes Mellitus (DM) is a chronic metabolic disease characterized by elevated blood glucose levels due to impaired insulin function. One of the chronic complications that often occurs is peripheral neuropathy, which is characterized by decreased foot sensitivity. Diabetic foot exercises are a non-pharmacological therapy that can help improve blood circulation and improve peripheral nerve function. To improve patients' knowledge and ability to perform foot exercises and observe their effects on foot sensitivity and blood glucose levels. Community service activities were carried out using the methods of socialization, demonstration, and evaluation of 20 type 2 DM patients in the Rengasdengklok ward of Karawang Regional Hospital. Activities included counseling, foot exercise practice, and blood glucose level checks before and after the intervention. Participants showed an increase in knowledge from 62% to 92%. After performing foot exercises regularly for three days, there was a decrease in blood glucose levels by an average of 20–30 mg/dL and increased foot sensitivity. Socialization of the application of foot exercises effectively increased the knowledge and ability of type 2 DM patients and helped lower blood glucose levels and improve foot sensitivity.